Phosphorylation-Regulated Transitions in an Oligomeric State Control the Activity of the Sae2 DNA Repair Enzyme - Fu, Qiong (American Society for Microbiology, 2014)
In the DNA damage response, many repair and signaling molecules mobilize rapidly at the sites of DNA double-strand breaks. This network of immediate responses is regulated at the level of posttranslational modifications that control the activation of DNA processing enzymes, protein kinases, and scaffold proteins to coordinate DNA repair and checkpoint signaling. Here we investigated the DNA damage-induced oligomeric transitions of the Sae2 protein, an important enzyme in the initiation of DNA double-strand break repair. Sae2 is a target of multiple phosphorylation events, which we identified and characterized in vivo in the budding yeast Saccharomyces cerevisiae. Both cell cycle-dependent and DNA damage-dependent phosphorylation sites in Sae2 are important for the survival of DNA damage, and the cell cycle-regulated modifications are required to prime the damage-dependent events. We found that Sae2 exists in the form of inactive oligomers that are transiently released into smaller active units by this series of phosphorylations. DNA damage also triggers removal of Sae2 through autophagy and proteasomal degradation, ensuring that active Sae2 is present only transiently in cells. Overall, this analysis provides evidence for a novel type of protein regulation where the activity of an enzyme is controlled dynamically by posttranslational modifications that regulate its solubility and oligomeric state.